Investigating The Relationship Between Financial Factors And P/E Ratio Of Listed Steel Companies On Vietnam Stock Exchange - Nguyen Van, Quan; Bui Do Huyen, My; Bui Doan Gia, Binh (International Journal of Scientific Research and Management (IJSRM), 2024)
The importance of the steel industry and its continuous development for steel companies in developing countries may lead to potential investment opportunities for investors in the stock markets. With the direct impact of financial indicators, this study was conducted with the main purpose to investigate the relationship between financial factors and price-to-earnings (P/E) ratio of listed steel companies on Vietnam Stock Exchange. The research was conducted with quantitative method through collecting secondary data with 13 listed businesses in the period of 2013-2022. The findings indicated that dividend payout ratio, earnings growth and stock price respectively have a decreasing positive impact on P/E ratio. In contrast, earnings per share shows a non statistical relationship with P/E. This will be an important basis for proposing management and policy implications for policy makers, businesses and investors to promote favorable a stock investing environment through a wise assessment of P/E ratio.